Upaya Meningkatkan Motivasi Belajar dan Hasil Belajar Ekonomi dengan Menggunakan Model Student Team Achievement Division (STAD) pada Kelas X di SMA Negeri 1 Katingan Hilir - Yulisa Septiana; Muhammad Jailani (Neraca: Jurnal Pendidikan Ekonomi, 2019)
This study aims to, 1) Know the activities of students, 2) Know the learning motivation of students, 3) Increase the results of learning Economics after using the STAD Model on students of class X6 of Katingan Hilir 1 High School. This type of research is the Class Action Research (CAR). The type of model used is the STAD Model. The subjects of this study were students of class X 6 of Katingan Hilir 1 Senior High School, totaling 22 students as well as research samples. Data collection techniques used are observation, tests, and documentation. Data analysis techniques are based on the results of the cycle during the learning process. The results of the study show that: 1) The activity of students increases and is better. This is indicated by the learning activities of the first cycle which scored 58.65 (2.67) which increased in the second cycle with a score of 78.67 (3.58). 2) The learning motivation of students increases, this is shown from the observation sheet cycle I obtaining a score of 62.66 (22.85) increasing in the second cycle with a score of 72.06 (3.28). 3) There is an increase in student learning outcomes by using the Student Team Aiviement Divison (STAD) model. This is intended from the learning outcomes of students in the first cycle of 72.31 (72.27%) increasing in the second cycle to 78.3 (100%).